Career decisions for vocational students through self-efficacy development in the form of electronic publications - Karina Karina; Moch. Irtadji; Muslihati Muslihati; Eko Pramudya Laksana (Psychology, Evaluation, and Technology in Educational Research, 2021)
Career decisions making is an important thing. Today, many media can be developed to help make the right career decision; one of them is an electronic publication. This research aims to establish an electronic publication (epub) of career decision-making self-efficacy guidance. The development model used was the Borg &Gall model. The initial try out reveals high product validity while the student tries out demonstrates a very accurate, practical, feasible, and fascinating interpretation. The results show that the epub formed career decision-making self-efficacy guidance has fulfilled the theoretical acceptance and practicality aspects; thus, it can be used by the counsellors and students in the career guidance program.